The theoretical investigation of global reactivity descriptors, NLO behaviours and bioactivity scores of some norbornadiene derivatives - Serpil Eryılmaz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, global reactivity descriptors such as ionization potential, electron affinity, electronegativity, chemical hardness, softness and electrophilicity index of norbornadiene derivatives which include some halogen atoms and atom groups, have been investigated with DFT/BPV86/B3LYP/B3PW91 methods with 6-31G(d,p) basis set. To determine the non-linear optical behaviours of the structures, the total dipole moment, polarizability,and first-order hyperpolarizabilityvalues have been examined at the same theoretical level. It has been determined that thiol-bonded groups on comparison with others have a much better NLO material property. In addition, the potentials of the structures as drug-active compounds have been inspected with Lipinski’s rule of 5 and bioactivity scores. Thiol and hydroxyl-bonded groups have a good drug-likeness and bioactivity score relative to the others.